Optimization of Spot Welding Parameters on Shear Tensile Strength of 0.9 mm SPCC Material using the Taguchi Methods - Samodra, Yudha; Hutama, Adhi Setya; Kurniawan, Perwita; Hayu, Winastwan Sista; Nugroho, Th. Adi (Jurnal Rekayasa Mesin, 2025)
Resistance spot welding (RSW) is one of the most widely used joining methods for thin metal sheets in the manufacturing industry, particularly for low-carbon steel materials such as SPCC. At PT. XYZ, inconsistencies in weld quality have been observed due to the absence of optimized process parameters. This study aims to analyze the influence of spot welding parameters—welding current, welding time, and holding time—on the shear tensile strength of 0.9 mm SPCC material. The Taguchi method with an L9 orthogonal array experimental design was employed to identify the optimal parameter combination. Shear tensile testing was conducted in accordance with ISO 14273:2016, while data analysis was performed using the Signal-to-Noise (S/N) ratio with the "larger is better" criterion and Analysis of Variance (ANOVA).The results indicate that welding current is the most dominant factor, contributing 71.12% to the variation in shear tensile strength, followed by welding time at 21.11%, while holding time has a relatively minor contribution of 5.66%. The optimal condition was achieved at 34 kA (welding current), 15 cycles (welding time), and 10 cycles (holding time), yielding a maximum shear tensile strength of 572.06 kgf and an S/N ratio of 54.00 dB. This study demonstrates that the Taguchi method is effective for optimizing spot welding parameters with a minimal number of experiments, providing a reliable technical guideline to improve the quality and consistency of production processes in the manufacturing industry.